A low electromotive force sodium-ion battery without negative electrode based on sodium-compensated positive electrode and a preparation method thereof

CN122843352APending Publication Date: 2026-09-29SHANGHAI WEINA NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611331047.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

然而,上述方法均为被动调控策略,并未从源头上改变钠沉积过程的热力学和动力学条件

Benefits of technology

本发明通过正极材料的预补钠设计,在首次充电低电压阶段(1.88 V~2.5 V)即可释放预存储的过量钠离子。这些钠离子专用于补偿负极集流体表面SEI膜形成所需的不可逆钠消耗,确保正极主体结构中基准钠离子(对应于x=0部分)在后续正常充放电过程中得以完整保留并发挥容量贡献。相比常规无负极电池中正极钠源被SEI形成大量消耗而导致容量损失的状况,本发明可显著提高首次库仑效率,实施例数据显示其ICE值可达96%以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122843352A_ABST
    Figure CN122843352A_ABST
Patent Text Reader

Abstract

This invention relates to the field of electrochemical energy storage technology, and in particular to a low electromotive force, negative electrode-free sodium-ion battery based on a sodium-compensated positive electrode and its preparation method. The positive electrode active material of the battery is Na... 2 / 3+X Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 sodium compensation P2 type layered oxide, of which 0.05
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, and in particular to a low electromotive force sodium-ion battery without a negative electrode based on a sodium-compensated positive electrode and its preparation method. Background Technology

[0002] Due to the abundance, wide distribution, and low cost of sodium resources, sodium-ion batteries have broad application prospects in the field of large-scale electrochemical energy storage. To pursue higher energy density, anode-free sodium metal battery structures have been proposed. In this structure, the negative electrode side does not contain an active sodium source or negative electrode active material; instead, a metal current collector (such as aluminum foil) is directly used. During charging, metallic sodium is electrochemically deposited on the surface of the current collector to form the negative electrode, and during discharge, sodium dissolves from the surface of the current collector. This structure can significantly improve the volumetric energy density and gravimetric energy density of the battery.

[0003] However, sodium-ion batteries without negative electrodes face two key challenges in their practical application.

[0004] Firstly, there is the issue of irreversible loss of active sodium. During the initial charge, sodium ions released from the positive electrode migrate to the surface of the negative electrode current collector, where a reduction reaction occurs at the current collector / electrolyte interface. Simultaneously, the electrolyte decomposes to form a solid electrolyte interphase (SEI) film. The formation of the SEI film continuously consumes the active sodium ions provided by the positive electrode, resulting in a significantly lower initial coulombic efficiency of the battery. Since the negative electrode-less battery structure does not contain an additional source of active sodium, this irreversible loss directly leads to a substantial reduction in the battery's reversible capacity, becoming one of the core bottlenecks limiting its cycle life.

[0005] Secondly, there is the issue of uneven sodium deposition and dendrite growth. In a negative electrode-less configuration, the nucleation and growth behavior of sodium on the planar current collector surface has a decisive impact on battery safety. During charging, sodium ions are reduced on the current collector surface to form sodium atoms, which then aggregate into crystal nuclei and grow into a metallic sodium deposition layer. Due to the unavoidable microscopic inhomogeneities on the current collector surface (such as roughness, defects, impurities, etc.), the local current density distribution of sodium ions is uneven, leading to uneven sodium nucleation. During continuous charging, further sodium deposition preferentially occurs at the uneven nucleation sites, forming dendritic or moss-like sodium dendrites. The growth of sodium dendrites can penetrate the separator and reach the positive electrode, causing serious safety problems such as internal short circuits and thermal runaway; at the same time, the dendrite structure is loose and easily detaches from the current collector during discharge, forming "dead sodium," leading to continuous capacity decay and fluctuations in coulombic efficiency.

[0006] To address the above problems, several improvement solutions have been proposed in the existing technology.

[0007] To compensate for active sodium loss, one strategy is to add sodium compensation additives (also known as "sacrificial sodium sources") to the positive electrode, such as NaN3, Na2C2O4, and Na2CO3. These additives undergo irreversible decomposition at a specific potential during the first charge, releasing additional sodium ions to compensate for the capacity loss caused by SEI formation. However, this strategy has significant limitations: most sodium compensation additives have high decomposition potentials, which do not match the operating potential range of conventional positive electrode materials; decomposition products (such as gases) remaining inside the battery may pose safety hazards; and the introduction of additives also reduces the mass ratio of the positive electrode active material, sacrificing the overall energy density of the battery.

[0008] Existing technologies for suppressing sodium dendrite growth mainly focus on modifying the surface of the negative electrode current collector, optimizing the electrolyte formulation, and functionalizing the separator. For example, carbon coating, metal oxide coating, or sodium affinity treatment on the aluminum foil surface can improve the wettability of the current collector to sodium and the uniformity of nucleation; adjusting the electrolyte salt concentration and adding nucleation promoters can alter the deposition behavior of sodium. However, these methods are all passive control strategies and do not fundamentally change the thermodynamic and kinetic conditions of the sodium deposition process.

[0009] The existing technology has not fully recognized the decisive influence of the electromotive force (EMF) in the early stage of battery charging on the sodium deposition morphology, and there is also a lack of technical solutions to actively create a low EMF environment through cathode material design to synergistically achieve sodium compensation and uniform deposition. Summary of the Invention

[0010] To address the two major technical challenges of irreversible active sodium loss and sodium dendrite growth in existing electrodeless sodium-ion batteries, this invention provides a low EMF electrodeless sodium-ion battery based on a sodium-compensated positive electrode and its preparation method. This invention aims to simultaneously achieve efficient sodium compensation and the construction of a low EMF sodium deposition environment during the first charge process through innovative design of the positive electrode material, thereby comprehensively improving the initial coulombic efficiency, cycle stability, and safety of the electrodeless sodium-ion battery.

[0011] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A low electromotive force sodium-ion battery without a negative electrode based on a sodium-compensated positive electrode includes a positive electrode, a negative electrode current collector, a separator disposed between the positive electrode and the negative electrode current collector, and a sodium salt electrolyte. The active material of the positive electrode is a P2-type layered oxide with sodium compensation properties, and its general formula is Na. 2 / 3 +xNi 1 / 3Mn 1 / 3 Ti 1 / 3 O2, of which 0.05 <x≤0.4; The sodium-compensated P2-type layered oxide is prepared by a pre-sodium-compensated method, and it is in the P2-Na 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / The 3O2 crystal structure exhibits pre-intercalation of excess sodium ions, resulting in reversible superstoichiometric sodium ion insertion / extraction capabilities. This material demonstrates strong performance during the initial battery charge to 2.5V (vsNa). + During the process of (Na), pre-stored excess sodium ions can be released in a low voltage range of 1.88V to 2.5V. These released sodium ions migrate to the surface of the negative electrode current collector. Some are consumed in the interfacial reaction to form an SEI film, compensating for irreversible capacity loss, while the rest are deposited on the current collector surface in the form of metallic sodium to form the negative electrode active layer.

[0012] From an electrochemical thermodynamics perspective, the deposition potential of sodium ions on the negative electrode current collector is directly related to the electromotive force (EMF) of the battery system. In conventional negative electrodeless batteries, the initial charge removal of sodium from the positive electrode structure typically requires a higher voltage, corresponding to a higher system EMF. Under high EMF conditions, the sodium ion concentration gradient at the negative electrode current collector / electrolyte interface increases, forming significant concentration polarization. Simultaneously, the high overpotential provides a strong driving force for the three-dimensional nucleation of sodium atoms on the current collector surface, resulting in low nucleation site density and non-uniform nucleus size, thereby inducing dendritic growth. In this invention, the sodium-compensated positive electrode releases sodium ions in the low voltage range of 1.88V to 2.5V, a process corresponding to the low EMF state of the battery system. Under low EMF conditions, the concentration polarization at the interface is significantly reduced, and the sodium ion flux distribution is more uniform. The reduction in overpotential decreases the nucleation barrier and increases the effective nucleation site density, thereby inducing metallic sodium to deposit on the current collector surface in a fine, uniform, and dense morphology, effectively suppressing dendrite initiation and growth.

[0013] After completing the aforementioned low-voltage sodium replenishment stage, the battery voltage can continue to rise to the normal operating range. Reference sodium ions in the x=0 portion of the positive electrode are further removed, supporting subsequent normal charge-discharge cycles. Since the sodium loss required for SEI formation has been fully compensated by pre-stored sodium ions during the low-voltage stage, and the sodium layer structure formed during the initial deposition is uniform and dense, the sodium deposition / dissolution behavior in subsequent cycles maintains good reversibility, significantly improving the battery's cycle stability and coulombic efficiency.

[0014] Furthermore, the value of x is preferably from 0.15 to 0.35, and more preferably x ≈ 0.255. This preferred range, by controlling the amount of pre-embedded sodium, achieves sufficient sodium compensation while avoiding irreversible damage to the P2 layered structure caused by excessive sodium embedding, thus balancing the structural stability and sodium replenishment capacity of the material.

[0015] In this invention, the negative electrode current collector can be aluminum foil, aluminum foil with carbon coating, copper foil, or a metal current collector that has undergone sodium affinity treatment. Aluminum foil has significant advantages as a current collector in negative electrode-free batteries due to its low cost, light weight, and lack of alloying reaction with sodium; carbon coating or sodium affinity treatment can further improve the wettability of the current collector surface to sodium and the uniformity of nucleation.

[0016] The sodium salt in the sodium salt electrolyte can be selected from sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), or sodium bis(trifluoromethanesulfonyl)imide (NaTFSI); the sodium salt electrolyte can be an organic liquid electrolyte, a gel polymer electrolyte, or a solid electrolyte. When an organic liquid electrolyte is used, its solvent can be selected from one or more of ethylene carbonate (EC), diethyl carbonate (DEC), and propylene carbonate (PC), or from one or more of 1,3-dioxolane (DOL) and dimethyl ethylene glycol (DME). Ether electrolytes have better interfacial compatibility with metallic sodium, which is beneficial for further improving the sodium deposition morphology.

[0017] The present invention also provides two methods for preparing the sodium-compensated positive electrode, namely, a chemical pre-sodium supplementation method and an electrochemical pre-sodium supplementation method.

[0018] The chemical pre-sodium supplementation method includes the following steps: a) Solution preparation: In an inert atmosphere glove box, dissolve the organic sodium reagent in an anhydrous and oxygen-free aprotic organic solvent and stir to prepare an organic sodium solution with a concentration of 0.1M to 2.0M. b) Pre-sodium supplementation reaction: P2-Na 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 The O2 positive electrode sheet is immersed in the organic sodium solution prepared in step a) and reacted at 15°C to 30°C for 1 to 120 minutes. c) Washing: Remove the positive electrode after the reaction and wash it multiple times with anhydrous and oxygen-free washing solvent; d) Drying: The washed positive electrode sheet is vacuum dried at 60°C to 120°C under an inert atmosphere to obtain the sodium-compensated positive electrode.

[0019] In the above-described chemical pre-sodium replenishment method, the organic sodium reagent in step a) is a strongly reducing organic sodium compound with a suitable reduction potential, specifically selected from one or more of sodium-benzophenone, sodium-naphthalene, and sodium-biphenyl; the aprotic organic solvent is selected from one or more of tetrahydrofuran (THF), dimethyl glycol ether (DME), and dimethyl ethylene glycol ether (Diglyme). The above-described organic sodium reagent can form a soluble sodium complex in an aprotic solvent, possessing a suitable reduction potential, which can drive sodium ions to intercalate into the P2 structural interlayer without extreme reaction conditions. By adjusting the concentration of the organic sodium solution (0.1M~2.0M) and the reaction time (1~120 minutes), the degree of sodium replenishment, i.e., the x-value, can be precisely controlled.

[0020] In step c), the washing solvent may be selected from one or more of tetrahydrofuran, ethylene glycol dimethyl ether, and dimethyl carbonate. The washing operation typically needs to be repeated until the washing solution is colorless and transparent to ensure complete removal of residual organic sodium reagents and reaction byproducts.

[0021] In step d), the drying temperature is preferably 80°C, and the drying time is usually 6 to 24 hours.

[0022] The electrochemical pre-sodium replenishment method includes the following steps: i. Take P2-Na 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 is used as the positive electrode and metallic sodium as the negative electrode to assemble a half-cell; ii. Discharge the half-cell to the target capacity at a rate of 0.05C to 0.2C to achieve the required sodium replenishment level x; iii. Disassemble the discharged half-cell in an inert atmosphere glove box and remove the positive electrode after sodium replenishment; iv. Wash the positive electrode sheet with anhydrous and oxygen-free dimethyl carbonate and dry it to obtain the sodium-compensated positive electrode.

[0023] The advantage of the electrochemical pre-sodium replenishment method is that the amount of sodium replenishment can be precisely controlled by the discharge capacity, which is beneficial to the consistency and repeatability of material preparation.

[0024] This invention also protects the application of the above-mentioned negative electrode-free sodium-ion battery in large-scale energy storage systems, electric vehicles, or portable electronic devices.

[0025] The technical effects and advantages of this invention are as follows: This invention utilizes a pre-supplemented sodium design in the positive electrode material to release pre-stored excess sodium ions during the low-voltage phase of the initial charge (1.88 V~2.5 V). These sodium ions are specifically used to compensate for the irreversible sodium consumption required for the formation of the SEI film on the surface of the negative electrode current collector, ensuring that the reference sodium ions in the main positive electrode structure (corresponding to the x=0 portion) are fully retained and contribute to capacity during subsequent normal charge and discharge processes. Compared to the capacity loss caused by the significant consumption of the positive electrode sodium source during SEI formation in conventional negative electrode-less batteries, this invention significantly improves the initial coulombic efficiency, with example data showing an ICE value exceeding 96%.

[0026] This invention reveals for the first time the intrinsic correlation between the initial electromotive force (EMF) of a battery system and the sodium deposition morphology, and based on this, realizes a technical path for actively controlling sodium deposition behavior through cathode material design. The sodium release process in the low voltage range (1.88 V~2.5 V) provides a low EMF charging environment for the battery, effectively reducing concentration polarization and deposition overpotential at the negative electrode current collector / electrolyte interface. The low overpotential facilitates the formation of high-density nucleation sites, inducing the deposition of metallic sodium in a uniform, fine-grained, and dense morphology, thus suppressing dendrite initiation at its source. The uniform and dense initial deposition layer lays a good foundation for the reversible dissolution / deposition of sodium in subsequent cycles, significantly improving the battery's cycle stability.

[0027] This invention solves two core challenges of anode-less sodium-ion batteries—sodium source compensation and dendrite suppression—through innovative design of a single cathode material. It eliminates the need for additional sacrificial additives, complex current collector pretreatment processes, and external control mechanisms. This technical solution is highly compatible with existing battery manufacturing processes and is easily scalable for industrial mass production.

[0028] The P2-type layered oxide Na used in this invention 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 possesses open sodium ion transport channels and good structural stability. Excess sodium ions pre-intercalated through chemical or electrochemical methods occupy interlayer sites, and after release at low voltage, the main layered structure is well maintained. It also exhibits good structural reversibility during subsequent charge and discharge processes, ensuring the long-term cycle performance of the battery. Attached Figure Description

[0029] Figure 1 This is a flowchart of the preparation method of the present invention; Figure 2 The figure shows the experimental results in an embodiment of the present invention. Detailed Implementation

[0030] The present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. The following embodiments are for illustrative purposes only and should not be construed as limiting the scope of protection of the present invention. Equivalent substitutions or modifications made by those skilled in the art based on the content of the present invention are all within the scope of protection of the present invention.

[0031] Example 1: Preparation of NRP2 cathode material by chemical pre-sodium supplementation method 1. Precursor P2-Na 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 synthesis P2-Na synthesized by sol-gel method 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 precursor. Sodium acetate (NaAc, 99.5%), nickel acetate (Ni(Ac)2·4H2O, 98%), manganese acetate (Mn(Ac)2·4H2O, 98%), and tetrabutyl titanate (Ti(OC4H9)4, 99%) were weighed according to stoichiometric ratio and dissolved in deionized water. Citric acid was added as a complexing agent, and the mixture was stirred and evaporated in an 80°C water bath to form a gel. The gel was dried at 120°C and then calcined in air at a heating rate of 5°C / min to 900°C for 12 hours. After furnace cooling, the calcined gel was ground to obtain P2-Na. 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 powder.

[0032] 2. Preparation of the positive electrode sheet The above-mentioned P2-NaNMT active material, conductive carbon black (SuperP), and polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent. The mixture was magnetically stirred for 4 hours to form a uniform slurry. The slurry was then uniformly coated onto an aluminum foil current collector with a thickness of 16 μm using a doctor blade method, with the coating thickness controlled at 150 μm. The coated electrode was dried in a vacuum oven at 80°C for 12 hours, compacted by a roller press, and then punched into circular positive electrode sheets with a diameter of 12 mm. The active material loading was approximately 1.5~2.0 mg / cm³. 2 .

[0033] 3. Preparation of sodium biphenyl solution In a high-purity argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), different masses of biphenyl (C 12 H 10Biphenyl-THF solutions with concentrations of 0.25 M, 0.5 M, 1.0 M, and 1.5 M were prepared by dissolving 99.5% of a biphenyl compound in anhydrous tetrahydrofuran (THF, H2O < 10 ppm). Excess sodium metal flakes (99% purity) were added to each solution, and the mixture was magnetically stirred at room temperature for 12 hours until the solution color stabilized at a deep blue, indicating that the sodium biphenyl complex (Na-C) was formed. 12 H 10 The solution has fully formed. After standing, collect the supernatant for later use.

[0034] 4. Chemical pre-sodium supplementation reaction The P2-NaNMT positive electrode was immersed in sodium biphenyl solutions of different concentrations (0.25M, 0.5M, 1.0M, and 1.5M) and reacted for 5, 15, 30, 60, and 120 minutes at room temperature (25°C ± 2°C). The entire reaction was carried out in an argon-filled glove box. During the reaction, the solution color gradually lightened from dark blue, indicating the consumption of sodium biphenyl reagent and the insertion of sodium ions into the positive electrode material.

[0035] 5. Washing and drying After the reaction was complete, the electrode was removed from the sodium biphenyl solution and immediately transferred to a beaker containing anhydrous THF for immersion and washing for 3 minutes. This washing was repeated 3 times, with fresh THF solvent each time, until the washing solution was colorless and transparent, to thoroughly remove residual sodium biphenyl, by-reaction products, and adsorbed solvent from the surface and internal pores of the electrode. The washed electrode was then vacuum-dried at 80°C for 12 hours in an argon glove box to obtain sodium-compensated P2-type cathode materials with different sodium compensation levels, labeled as NRP2-5, NRP2-15, NRP2-30, NRP2-60, and NRP2-120, where the numbers represent the reaction time (minutes).

[0036] The molar ratio of Na / (Ni+Mn+Ti) in each sample was determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the corresponding x value was calculated. The results are shown in Table 1.

[0037] Table 1. Sodium replenishment levels of NRP2 samples under different reaction conditions. Example 2: Preparation of NRP2 cathode material by electrochemical pre-sodium supplementation method In an argon glove box, a CR2032 coin cell was assembled using the unsupplemented sodium P2-NaNMT positive electrode prepared in Example 1 as the working electrode, a sodium metal sheet (thickness 0.3 mm, purity 99.9%) as the counter electrode, a glass fiber membrane (Whatman GF / D) as the separator, and a solution of 1M NaPF6 dissolved in ethylene carbonate / diethyl carbonate (EC / DEC, volume ratio 1:1) as the electrolyte.

[0038] The assembled half-cell was placed on the Blue Battery Testing System and discharged at a constant current of 0.1C (1C=90mA / g) to different cutoff capacities. The discharge capacities were controlled to be 5%, 15%, 30%, 50%, and 80% of the theoretical sodium-replenished capacity (based on the mass of active material), respectively. After discharge, the battery was disassembled in a glove box, the positive electrode was removed, and washed three times with anhydrous dimethyl carbonate (DMC) to remove residual electrolyte. It was then vacuum dried at 80°C for 6 hours in an argon atmosphere to obtain the electrochemically pre-sodium-replenished NRP2 positive electrode material.

[0039] The x-value obtained by the electrochemical pre-sodium replenishment method can be accurately calculated from the discharge capacity, and the deviation from the target value is controlled within ±2%. This method is superior to the chemical method in terms of precise control of sodium replenishment.

[0040] Example 3: Assembly and electrochemical performance testing of a sodium-ion battery without a negative electrode 1. Battery assembly The positive electrode used was the NRP2-30 (x=0.255) positive electrode sheet prepared in Example 1. The negative electrode current collector was made of 16μm thick aluminum foil, which was placed in an argon glove box for use before assembly. The separator was a glass fiber membrane (Whatman GF / D). The electrolyte was an ether electrolyte consisting of 1M NaPF6 dissolved in diethylene glycol dimethyl ether (diglyme, H2O <10ppm).

[0041] In an argon-filled glove box, CR2032 coin cells were assembled in the following order: negative electrode shell—negative electrode current collector (aluminum foil)—separator (with 80 μL of electrolyte added)—positive electrode plate—gasket—spring plate—positive electrode shell. After assembly, the cells were sealed using a sealing machine to obtain an Al||NRP2-30 negative electrode-free sodium-ion battery. For comparison, an Al||P2-NaNMT negative electrode-free battery with unadded sodium P2-NaNMT as the positive electrode was also assembled as a control example.

[0042] 2. Electrochemical testing The assembled battery was placed in a 25°C constant temperature chamber for 6 hours before charge-discharge testing. The charge-discharge voltage range was 1.0V to 4.0V (vsNa). + / Na), charge / discharge current density of 0.1C (based on the mass of positive electrode active material, 1C=90mA / g), 50 cycles.

[0043] 3. Initial charge / discharge characteristics The initial charge curve of the Al||NRP2-30 battery shows a distinct low-voltage plateau at approximately 1.88V, corresponding to the release of excess sodium ions pre-stored in the NRP2 cathode. The sustained charging capacity at this plateau is approximately 32 mAh / g (based on the mass of the cathode active material), which is largely consistent with the theoretical sodium replenishment capacity (approximately 36 mAh / g for x=0.255). After the plateau, the voltage continues to rise above approximately 2.5V, corresponding to the normal release of sodium ions from the interlayer of the P2 structure.

[0044] In contrast, the Al||P2-NaNMT comparative battery rapidly climbed to over 2.8V during the initial charging phase, without exhibiting a low-voltage plateau characteristic. This indicates that a higher potential is required for sodium ions to escape from the host structure, corresponding to a higher system EMF.

[0045] 4. First Coulomb Efficiency The Al||NRP2-30 battery exhibited an initial charge specific capacity of 124.6 mAh / g and an initial discharge specific capacity of 118.2 mAh / g, resulting in an initial coulombic efficiency of 94.9%. In contrast, the Al||P2-NaNMT comparative battery showed an initial charge specific capacity of 96.8 mAh / g and an initial discharge specific capacity of 76.3 mAh / g, with an initial coulombic efficiency of only 78.8%. These results indicate that the additional sodium source provided by the pre-added sodium cathode effectively compensates for the active sodium consumed in SEI formation, significantly improving the initial coulombic efficiency of the electrodeless battery.

[0046] 5. Cyclic stability like Figure 2 As shown, the Al||NRP2-30 battery retained 97.4% of its capacity after 50 cycles (based on the initial discharge specific capacity); the comparative battery, however, retained only 52.7% of its capacity after 50 cycles. The coulombic efficiency of the comparative battery fluctuated significantly during cycling, while the coulombic efficiency of the NRP2 battery remained consistently above 99.5%, further validating the structural stability and reversibility of the uniform sodium deposition layer formed under low EMF during long-term cycling.

[0047] 6. Characterization of sodium deposition morphology After initial charging to different cutoff states, the batteries were disassembled in a glove box, the negative electrode current collector was removed, and residual electrolyte was removed by washing with DMC. The sodium deposition morphology was observed using a scanning electron microscope (SEM). The sodium deposition layer of the Al||NRP2-30 battery exhibited a uniform, dense granular morphology with a narrow grain size distribution (approximately 0.5–1.5 μm) and a smooth surface without dendrite features. The sodium deposition layer of the Al||P2-NaNMT comparative battery exhibited a loose, porous dendritic morphology with uneven grain size (approximately 0.2–5 μm) and sharp protrusions in localized areas.

[0048] Example 4: The effect of different x values ​​on battery performance Following the method in Example 1, NRP2 cathode materials with x = 0.08, 0.18, 0.255, 0.32, and 0.38 (corresponding to NRP2-5, NRP2-15, NRP2-30, NRP2-60, and NRP2-120) were prepared respectively. Anode-free batteries were assembled according to the method in Example 3, and the effect of x value on battery performance was investigated. The results are shown in Table 2.

[0049] Table 2. Effects of different x values ​​on initial coulombic efficiency and cycle retention. The results show that when the x value is below 0.15, the sodium consumed in SEI formation cannot be fully compensated due to insufficient sodium supplementation, resulting in low initial coulombic efficiency and cycle retention. The overall performance is optimal when the x value is in the range of 0.15–0.35. When the x value exceeds 0.35, although sodium supplementation is sufficient, the irreversible effect of excessive sodium embedding on the P2 layered structure begins to appear, and the long-term cycle retention decreases slightly. x ≈ 0.255 (corresponding to a sodium supplementation of approximately 30% of the theoretical capacity) represents the optimal value for overall performance.

[0050] Example 5: The impact of electrolyte system on battery performance Following the battery assembly method of Example 3, Al||NRP2-30 negative electrode-free batteries were assembled using the following four electrolyte systems: Group A: 1M NaPF6 / EC:DEC (1:1 v / v) Group B: 1M NaPF6 / diglyme Group C: 1M NaClO4 / PC Group D: 1MNaTFSI / DOL:DME (1:1v / v) The initial coulombic efficiency and capacity retention after 50 cycles for the four types of batteries at 25°C are shown in Table 3.

[0051] Table 3 Battery performance under different electrolyte systems The above results indicate that the technical solution of the present invention is applicable to a variety of sodium salt and solvent systems, among which ether solvents (especially diglyme) have better compatibility with the sodium metal interface, which is beneficial to further improve the uniformity of sodium deposition and cycle stability.

[0052] Example 6: The Influence of Negative Electrode Current Collector Type on Battery Performance According to the battery assembly method of Example 3, the positive electrode is fixed as NRP2-30, and the following four types of negative electrode current collectors are used respectively: Pure aluminum foil (16μm thickness) Surface carbon-coated aluminum foil (carbon layer thickness approximately 2μm) Pure copper foil (12μm thick) Sodium-affinity treated aluminum foil (processed by chemical etching, surface roughness Ra≈0.3μm) The initial coulombic efficiency and capacity retention after 50 cycles for the four types of batteries are shown in Table 4.

[0053] Table 4 Battery performance under different negative electrode current collector types

[0054] The results show that the technical solution of this invention has good adaptability to different current collector types. Carbon coating and sodium affinity treatment can further improve the uniformity of sodium deposition, resulting in a slight improvement in cycle stability. Although copper foil can be used as a current collector, its interfacial bonding strength and wettability are slightly inferior to those of aluminum-based current collectors because sodium and copper do not undergo an alloying reaction.

[0055] The above are merely specific embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A low-electromotive force, negative-electrode-less sodium-ion battery based on a sodium-compensated positive electrode, comprising a positive electrode, a negative electrode current collector, a separator disposed between the positive electrode and the negative electrode current collector, and a sodium salt electrolyte; characterized in that, The active material of the positive electrode is a P2-type layered oxide with sodium compensation properties, and its general formula is Na. 2 / 3 +xNi 1 / 3 Mn 1 / 3 Ti 1 / 3 O2, of which 0.05 <x≤0.4; The sodium-compensated P2-type layered oxide is prepared by a pre-sodium-compensated method, and it is first charged to 2.5V (vs Na) in the battery. + During the process of / Na), pre-stored excess sodium ions can be released in a low voltage range of 1.88V to 2.5V; The released excess sodium ions migrate to the surface of the negative electrode current collector, part of which is used to form a solid electrolyte interface film, and the rest is deposited on the surface of the negative electrode current collector in the form of metallic sodium. The release of sodium ions in the low-voltage range provides a low electromotive force environment for the battery system, thereby reducing overpotential and concentration polarization during sodium deposition.

2. The negative electrode-free sodium-ion battery according to claim 1, characterized in that, The value of x is between 0.15 and 0.

35.

3. The negative electrode-free sodium-ion battery according to claim 1, characterized in that, The value of x is 0.

255.

4. The negative electrode-free sodium-ion battery according to claim 1, characterized in that, The negative electrode current collector is an aluminum foil, an aluminum foil with a carbon coating, a copper foil, or a metal current collector that has undergone sodium affinity treatment.

5. The negative electrode-free sodium-ion battery according to claim 1, characterized in that, The sodium salt in the sodium salt electrolyte is sodium hexafluorophosphate, sodium perchlorate, or sodium bis(trifluoromethanesulfonyl)imide; The sodium salt electrolyte is an organic liquid electrolyte, a gel polymer electrolyte, or a solid electrolyte; When the sodium salt electrolyte is an organic liquid electrolyte, its solvent is one or more of ethylene carbonate, diethyl carbonate, and propylene carbonate, or one or more of 1,3-dioxolane and ethylene glycol dimethyl ether.

6. A method for preparing a sodium-compensated positive electrode in a negative electrode-free sodium-ion battery according to any one of claims 1 to 3, wherein the active material of the sodium-compensated positive electrode is of the general formula Na. 2 / 3 +xNi 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 is a P2-type layered oxide, of which 0.05 <x≤0.4; The preparation method is a chemical pre-sodium supplementation method, which includes the following steps: a) Solution preparation: In an inert atmosphere, dissolve the organic sodium reagent in an anhydrous and oxygen-free aprotic organic solvent to prepare an organic sodium solution with a concentration of 0.1M to 2.0M; b) Pre-sodium supplementation reaction: P2-Na 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 The O2 positive electrode sheet is immersed in the organic sodium solution prepared in step a) and reacted at 15°C to 30°C for 1 to 120 minutes; c) Washing: Remove the positive electrode after the reaction and wash it with anhydrous and oxygen-free washing solvent; d) Drying: The washed positive electrode sheet is vacuum dried at 60°C to 120°C under an inert atmosphere to obtain the sodium-compensated positive electrode.

7. The preparation method according to claim 6, characterized in that, In step a), the organic sodium reagent is one or more of sodium-benzophenone, sodium-naphthalene, and sodium-biphenyl; the aprotic organic solvent is one or more of tetrahydrofuran, ethylene glycol dimethyl ether, and dimethyl ethylene glycol ether.

8. The preparation method according to claim 6, characterized in that, In step c), the washing solvent is one or more of tetrahydrofuran, ethylene glycol dimethyl ether, and dimethyl carbonate.

9. A method for preparing a sodium-compensated positive electrode in a negative electrode-free sodium-ion battery according to any one of claims 1 to 3, wherein the active material of the sodium-compensated positive electrode is of the general formula Na. 2 / 3 +xNi 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 is a P2-type layered oxide, of which 0.05 <x≤0.4; The preparation method is an electrochemical pre-sodium replenishment method, including the following steps: i. Take P2-Na 2 / 3 Ni 1 / 3 Mn 1 / 3 Ti 1 / 3 O2 is used as the positive electrode and metallic sodium as the negative electrode to assemble a half-cell; ii. Discharge the half-cell to the target capacity at a rate of 0.05C to 0.2C to obtain the positive electrode after sodium replenishment; iii. Disassemble the half-cell in an inert atmosphere and remove the positive electrode after sodium replenishment; iv. Wash the sodium-compensated positive electrode sheet with anhydrous and oxygen-free dimethyl carbonate and dry it to obtain the sodium-compensated positive electrode.

10. The use of the negative electrode-free sodium-ion battery according to any one of claims 1 to 5 in energy storage systems, electric vehicles or portable electronic devices.